Does mistreatment during institutional childbirth increase the likelihood of experiencing postpartum depressive symptoms? A prospective cohort study in Nepal - Rejina Gurung; Miia Bask (Global Health Action)
Background Postpartum depression is associated with low socioeconomic status, adverse birthing processes, and life stress. Increasing evidence of mistreatment during childbirth, negative birth experiences, and poor quality of maternal care is of global concern. Objective To assess the risk of experiencing depressive symptoms among postpartum women exposed to mistreatment during institutional birthing in Nepal. Method We conducted a prospective cohort study from 29 March to 19 August 2022. Of 1629 women who gave birth in a hospital in Nepal, 1222 were assessed for mistreatment during childbirth and depressive symptoms using the Edinburgh Postnatal Depression Scale. We used binomial generalized linear mixed model to examine the risk ratio of postpartum depressive symptoms in women exposed to mistreatment during childbirth. Results The prevalence of postpartum depressive symptoms was 4.4%. Women exposed to mistreatment during childbirth were almost fifty percent more likely to have postpartum depressive symptoms (cRR 1.47; 95% CI 1.14, 1.89; p = 0.003) compared with the unexposed group. Furthermore, adolescent mothers exposed to mistreatment during childbirth had a seventy percent increased risk of depressive symptoms (aRR 1.72; 95% CI 1.23, 2.41; p = 0.002). Similarly, women who gave birth to female infants were thirty percent more likely to experience postpartum depressive symptoms (aRR 1.32; 95% CI 1.01–1.74; p = 0.039). Conclusion We observed an association between postpartum depressive symptoms and mistreatment during institutional births in Nepal. The implementation of appropriate respectful maternity care during childbirth and also routine screening for depressive symptoms is critical to improving perinatal mental health and well-being.